2015
DOI: 10.1111/1742-6723.12476
|View full text |Cite
|
Sign up to set email alerts
|

Survey of point of care ultrasound usage in emergency medicine by Vietnamese physicians

Abstract: Regular access to ultrasound machines increases the frequency of POCUS usage in EDs in Vietnam. POCUS training was not as clearly associated with POCUS usage as those without formal training were equally likely to use POCUS as those with formal training. No single POCUS application stood out as strongly preferred by physicians in this survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…In identifying perceived barriers to POCUS use, lack of equipment and education were the highest rated by a significant margin with 56% of respondents ranking them as “very important.” These results are similar to the findings of other surveys of US use in Vietnam and Kenya 11,12 . A survey performed in India of participants in a 4‐day US course in 2010 reported that 97% had “potential access” to an US machine in the near future, but this selection of participants at an emergency US course may not be representative of emergency physicians across India 13 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In identifying perceived barriers to POCUS use, lack of equipment and education were the highest rated by a significant margin with 56% of respondents ranking them as “very important.” These results are similar to the findings of other surveys of US use in Vietnam and Kenya 11,12 . A survey performed in India of participants in a 4‐day US course in 2010 reported that 97% had “potential access” to an US machine in the near future, but this selection of participants at an emergency US course may not be representative of emergency physicians across India 13 .…”
Section: Discussionsupporting
confidence: 83%
“…These results are similar to the findings of other surveys of US use in Vietnam and Kenya. 11,12 A survey performed in India of participants in a 4-day US course in 2010 reported that 97% had "potential access" to an US machine in the near future, but this selection of participants at an emergency US course may not be representative of emergency physicians across India. 13 Lack of access to US equipment in India is problematic since in addition to the usual issues with acquiring hospital equipment (cost, institutional approval, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In this study however, we found that male physicians used ultrasound more than their female colleagues. Other studies have also shown this, suggesting that male physicians are more likely to be early adopters of ultrasound [9,17]. Noteworthy, one study found that females felt they required more training compared to males to start using POCUS [18].…”
Section: Discussionmentioning
confidence: 87%
“…Critical care ultrasonography (CCUS) is a deliberately focused examination, aimed at rapidly answering straightforward clinical questions [1]. In the field of emergency and critical care medicine, CCUS is increasingly used to guide interventions in critically ill patients in various settings by experts and novices [2][3][4][5][6][7][8][9][10][11][12][13][14]. The training process required for users to attain competency in CCUS has varied widely between studies, reflecting the diversity in CCUS training between centers.…”
Section: Introductionmentioning
confidence: 99%